Chapter Alcune note su San Miniato in età medicea - CIPRIANI, GIOVANNI (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The link between San Miniato and the Medici, started in 1448 with the financing of the aedicule destined to host the miraculous crucifix of St. John Gualberto, continued with the artistic commissions of Pope Leo X. The contribution goes in particular into the transformations that the monastic complex underwent, at the behest of the family, during the siege of Florence in 1529-30 and in the following centuries, becoming first a vast fortress, then a lazaret; until the sacred value of the site was recovered from the early eighteenth century, with the creation of the Via Crucis and through the research of the bodies of the martyrs promoted by Grand Duke Cosimo III.